노즐 구경에 따른 초소수력 펠턴 터빈의 효율 및 성능 특성 - 조인찬; 박주훈; 김광호; 정진택; 김동익; 신유환 (한국유체기계학회, 2015)
This paper deals with performance characteristics and efficiencies of Pelton turbine can be applied as one of ERDs (Energy Recovery Devices) of PRO (Pressure Retarded Osmosis) system for desalination. The objective of this study is experimentally estimating the performance of micro-scale Pelton turbine for PRO pilot plant. Especially the performance characteristics with variations of jet nozzle diameter of Pelton turbine are discussed in detail. In order to do this, lab scale test rig of Pelton turbine was made for performance test, which includes water tank, Pelton wheel with buckets, jet nozzle and torque brake and so on. The parameter effects related on Pelton turbine’s efficiency were investigated and discussed on the influence of the variations of load and speed ratio.